2013
DOI: 10.1002/ccd.25265
|View full text |Cite
|
Sign up to set email alerts
|

A prospective intravascular ultrasound investigation of the necessity for and efficacy of postdilation beyond nominal diameter of 3 current generation DES platforms for the percutaneous treatment of the left main coronary artery

Abstract: The majority of patients with angiographic coronary atheroma have a mean LMS diameter of >4 mm indicating the requirement for post dilation beyond nominal diameter all of current generation DES in almost all patients when treating the LMS. This is achievable with current DES platforms with no intraprocedural complication. Clinical follow up indicates excellent short-term efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…When treating ULMCA lesions, the large (5.7 ± 0.7 [range 4–7.4] mm) LM diameter and the fractal anatomy (from LM to LAD or LCX) make it difficult the selection of the conventional DES diameter . IVUS data indicated that the mean maximal CSA of the LM range between 18 mm 2 (4.8 mm maximal diameter) and 23.3 mm 2 (5.5 mm maximal diameter) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When treating ULMCA lesions, the large (5.7 ± 0.7 [range 4–7.4] mm) LM diameter and the fractal anatomy (from LM to LAD or LCX) make it difficult the selection of the conventional DES diameter . IVUS data indicated that the mean maximal CSA of the LM range between 18 mm 2 (4.8 mm maximal diameter) and 23.3 mm 2 (5.5 mm maximal diameter) .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, current guidelines report a class IB recommendation for ULMCA disease with a SYNTAX score ≤22 and class IIa for ULMCA disease with a SYNTAX score 23–32 . Major features that may be responsible for the suboptimal success of PCI in ULMCA lesions are (1) the large diameter of the left main (LM), (2) the fractal anatomy (from LM to left anterior descending artery [LAD] or left circumflex artery [LCX]), and (3) involvement of the bifurcation, which still represents a predictor of restenosis . In order to adapt the conventional drug‐eluting stent (DES) with the fractal anatomy of the bifurcation, the proximal optimization technique (POT) is mandatory.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies 6,18,23,[26][27][28] did not have a primary focus on the clinical outcomes of non-complex LMCA disease treated with a single stenting technique. Only Agostoni, et al 22) reported that when ostial or mid-LMCA disease is treated with DES, the rate of cardiac events is particularly low.…”
Section: Discussionmentioning
confidence: 99%
“…In an ectatic or aneurysmal LMCA, only a few current stent designs can overcome disparate dimensions between the LMCA and its branches; the use of other stents might lead to deformation or substantial shortening of the stent platform. In one study of 125 patients who had significant left epicardial arterial stenosis, 6 the mean maximal diameter of the distal LM stem was 5.7 ± 0.7 mm (range, 4-7.4 mm), which would necessitate postdilating the DES platforms beyond the recommended diameterseven in conservative sizing-to attain good apposition.…”
Section: Discussionmentioning
confidence: 99%